Magnitude of the current in 2D interlayer tunneling devices. (15th January 2018) - Feenstra, Randall M; de la Barrera, Sergio C; Li, Jun; Nie, Yifan; Cho, Kyeongjae
Abstract: Using the Bardeen tunneling method with first-principles wave functions, computations are made of the tunneling current in graphene/hexagonal-boron-nitride/graphene (G/h-BN/G) vertical structures. Detailed comparison with prior experimental results is made, focusing on the magnitude of the achievable tunnel current. With inclusion of the effects of translational and rotational misalignment of the graphene and the h-BN, predicted currents are found to be about 15×  larger than experimental values. A reduction in this discrepancy, to a factor of 2.5×, is achieved by utilizing a realistic size for the band gap of the h-BN, hence affecting the exponential decay constant for the tunneling.